Heart failure with preserved ejection fraction in Belgium: characteristics and outcome of a real-life cohort. Issue 7 (2nd November 2021) - Lejeune, Sibille; Roy, Clotilde; Slimani, Alisson; Pasquet, Agnes; Vancraeynest, David; Beauloye, Christophe; Vanoverschelde, Jean-Louis; Gerber, Bernhard L.; Pouleur, Anne-Catherine
Abstract: Background: Due to aging of the population and the increase of cardiovascular risk factors, heart failure and preserved ejection fraction (HFpEF) is a rising health issue. Few data exist on the phenotype of HFpEF patients in Belgium and on their prognosis. Objectives: We describe clinical characteristics and outcomes of Belgian HFpEF patients. Methods: We prospectively enrolled 183 HFpEF patients. They underwent clinical examination, comprehensive biological analysis and echocardiography, and were followed for a combined outcome of all-cause mortality and first HF hospitalisation. Results: Belgian patients with HFpEF were old (78 ± 8 years), predominantly females (62%) with multiple comorbidities. Ninety-five per cent were hypertensive, 38% diabetic and 69% overweight. History of atrial fibrillation was present in 63% of population, chronic kidney disease in 60% and anaemia in 58%. Over 30 ± 9 months, 55 (31%) patients died, 87 (49%) were hospitalised and 111 (63%) reached the combined outcome. In multivariate Cox analysis, low body mass index (BMI), NYHA class III and IV, diabetes, poor renal function and loop diuretic intake were independent predictors of the combined outcome ( p  < .05). BMI and renal function were also independent predictors of mortality, as were low haemoglobin, high E/e' and poor right ventricular function. Conclusion: Belgian patients with HFpEF are elderly patients with a high burden of comorbidities. Their prognosis is poor with high rates of hospitalisation and mortality. Although obesity is a risk factor for developing HFpEF, low BMI is the strongest independent predictor of mortality in those patients.